Analysis of the thermoelectrical performance of samples made of Coir Agricultural Wastes combined with MWCNT - Gustavo Vera-Reveles; Jorge Simón; Edgar Briones; José Manuel Gutiérrez-Hernández; Francisco J. González; Gabriel González; Edmundo Cerda-Rodríguez; José Vulfrano González-Fernández (Scientific Reports, 2022)
Abstract A biomaterial made of coir and Multi-Walled Carbon Nanotubes (MWCNTs) is presented which exhibits a relatively high-Temperature Coefficient of Resistance (TCR) and thermal insulation properties. Bolometers usually offer acceptable thermal isolation, electrical resistance, and high TCR. Fibers from agricultural waste materials such as coir has a synergistic effect as thermal insulating material and noise reducer. Based on it, powdered coir pills were used as pilot samples, as well as 2 other samples with different dispersions of MWCNTs, sodium dodecyl benzene sulfonate (SDBS) and polyvinylpyrrolidone (PVP) solution. The 3 kinds of samples were thermo-electrically characterized to determine their bolometric performance. Thermal conductivity of k = 0.045 W/m K was obtained by solving the Fourier’s law substituting the data into the equation describing heat flux on the sample around room temperature. Results show that adding different concentrations of MWCNT to powdered coir will lead to films with lower electrical resistance, therefore the thermal conductivity increases while thermal resistance decreases. Finally, the bolometric performance shows a maximum peak with a relatively high TCR of − 40.4% at a temperature of 300.3 K, this synthesized material outperforms by almost 1 order of magnitude larger than commercial materials. Results in this work also indicate that it is possible to tune bolometric parameters of this kind of samples and to use them as thermal insulators in the construction industry, when building roofs and walls.